Memaksimalkan Peran Google Form dalam Kegiatan Belajar Mengajar di Era Covid-19 - Faroman Syarief; Kurniawan Prambudi Utomo; Muhammad Aziz Winardi Nasution; Fahmi Kamal (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2022)
The purpose of education is to form students to be able to increase the level of intelligence by transferring the knowledge and technology possessed by teachers. The purpose of this research is to provide understanding and knowledge in the computer field, especially the introduction of making questions through google form to educators at Madrasah Ibtidaiyah (MI) Muhajirin, Bekasi As for the problems that the school has during the current covid-19 pandemic, where some face-to-face learning is limited and some are still teaching online, so the lack of knowledge in applying some computer programs is still found and as well as a lack of understanding in making learning applications using the google form. The method used is through direct observation and interviews, so it is deemed necessary to provide training in the form of workshops to educators so that the results of this study are teachers u are able to create an interactive learning through the google form assignment method to become a capital to explore and expand knowledge in the field of technology